Gamified EFL Instruction: Empirical Evidence for Enhanced Language Proficiency, Learner Motivation, and Idealized Bilingual Identity - Ma, Xinyue (Journal of Research in Vocational Education, 2025)
In recent years, the integration of gamification into mobile-assisted language learning (MALL) has gained prominence, driven by technological advancements and the global popularity of platforms like Duolingo. These tools leverage game mechanics—such as points, rewards, and interactive challenges—to enhance engagement and motivation in language acquisition. Grounded in Csikszentmihalyi’s (2008) Flow Theory, which posited that optimal learning occurred when challenges aligned with learners’ skills, gamification aims to create immersive, enjoyable experiences that foster sustained participation. Despite growing evidence of gamification’s efficacy in improving language outcomes, limited research holistically examined its impact on psychological constructs such as motivation and the ideal L2 self, which were critical to fostering long-term motivation and self-perception in EFL contexts. This mixed-methods study addresses this gap by investigating how digital gamified language learning, via a mobile application, influences EFL learners’ language achievement, motivation, and idealized bilingual identity. The research involved 36 Chinese primary school learners divided into digital and non-digital gamified instruction groups over four months. Quantitative assessments of language proficiency, motivation and ideal L2 self were complemented by qualitative insights from semi-structured interviews. Results revealed that the digital gamified group significantly outperformed their non-digital counterparts in language achievement and ideal L2 self development, while also reporting heightened FLE. Qualitative analysis highlighted learners’ positive perceptions of gamification, emphasizing enhanced engagement, reduced anxiety, and collaborative learning opportunities. However, critiques emerged regarding limited vocabulary depth and insufficient interactive feedback. The findings aligned with the Self-Determination Theory, illustrating how gamification fulfills psychological needs for autonomy, competence, and relatedness, thereby fostering intrinsic motivation and flow states. Pedagogically, the study advocated for gamified tools as catalysts for learner-centric environments, though it underscored the necessity for richer content and adaptive feedback mechanisms. Limitations, including a small sample size and restricted qualitative scope, call for broader future research to generalize findings. This study bridged theoretical and practical gaps, demonstrating digital gamification’s potential to transform EFL instruction by merging enjoyment with efficacy, while offering actionable insights for educators, learners, and app developers to optimize language learning ecosystems.